Berlin as an 'Implicit' Metropolitan Space. Contradictions in the Institutional Construction of Scale. - Fricke, Carola; Gualini, Enrico (Routledge, 2019)
This chapter adopts an analytical-interpretive approach that compares the multiple ontologies of Berlin's metropolitan space, as they are expressed in policies' spatial scope and scale. The analysis thus builds on a methodology which attempts to go beyond a territorial-institutional perspective and to capture the construction of metropolitan scales in policy representations, discourses and practices, understood as metropolitan projects pursued by various actors. It moves from the role of public actors, taking into account the importance of institutional context for metropolitan rescaling by describing the multi-level governmental system in Berlin and Brandenburg. The core analysis then focuses on the explicit and implicit metropolitan projects expressed by different policies and the public and private actors involved, in order to map how understandings of the metropolitan space are constructed. The authors assume that these metropolitan projects are representative of a variety of practices and discourses with a specific, idiosyncratic definition of their metropolitan scope or scale of reference, which thereby contribute to constructing a particular understanding of metropolitan space. For this purpose, they compare strategic policy documents in the field of spatial planning and urban economic development. By this, they intend to understand the consistency and coexistence, but also the contradictions, and ultimately the competition for hegemony, which develops among understandings of metropolitan scale.
Keywords: Stadtentwicklung; Regionalplanung; Entwicklungsprogramm; Stadtwachstum; Metropole; Metropolregion; Raumentwicklung; Stadtraum; Stadtgröße; Stadtumland; Stadtregion; Akteur; Privatwirtschaft; Stadtverwaltung; Governance